Immersive language instruction: Teaching English through English to non-native speakers - Paramita, Ratri; Zulfan, Muhammad; Agustini, Ni Putu Oka (Journal of Applied Studies in Language, 2024)
This study investigates the effectiveness of using English as the sole medium of instruction in teaching English to non-native speakers. The main goal is to evaluate how this method improves language proficiency, particularly in terms of fluency, comprehension, and confidence. The study adopts a qualitative approach, utilizing observations and interviews with both teachers and students from secondary schools that implement English-only instruction. Data were collected over a six-month period, followed by thematic analysis to uncover the key advantages and challenges of this teaching approach. Findings reveal that students exposed to exclusive English instruction demonstrate better fluency and listening comprehension compared to their peers in bilingual learning environments. Moreover, increased interaction between teachers and students in English was observed, creating a more immersive and engaging learning experience. Despite these benefits, the study also identified challenges, such as initial student discomfort and difficulties in grasping complex instructions. In conclusion, while teaching English exclusively in English is an effective strategy for enhancing language acquisition, it requires thoughtful support to accommodate varying levels of student proficiency. Future studies could explore the lasting effects of this method on students' academic performance.